Colombian regulations on hiring personnel : focus on decent work and soft skills. (2022)
As Colombia is a social state based on the rule of law, the wide normative that regulates the topics includes the labor component that must be taken into account from the incorporation of the personnel in the organizations; the Onboarding defined as the process of integration of the new collaborator in the company, strategy that the authors have been working on to be implemented in the ESE Santiago de Tunja, is a key factor in the business development and its detailed study, has a direct impact on the spirit of the organization. The following document presents a normative review of the contractual link between worker and company; the normative is structured as a normogram, under the categorical cross technique (which is explained in the development of the research) and is focused on the Health sector. The review also presents a direct relationship with two additional topics: decent and dignified work and soft skills as a topic integrated to labor linkage and integration (Onboarding) and productive development. The descriptive review was carried out based on the institutional tools of the Public Function Normative Manager, and databases such as Scopus and Google Scholar. The analysis of the regulations revealed contradictions in their application in relation to their development, finding in the Colombian case a high percentage of workers who are not hired directly but through other forms of non-labor and outsourcing, which results in a precariousness of the worker's conditions and deteriorates the policy of decent and dignified work, a situation that is widespread in the country.